Cultural integration of immigrants in Europe - Algan, Yann. (Oxford : Oxford University Press, 2012)
Taking an economic perspective, this edited collection presents a current, comparative picture of the process of cultural integration of immigrants across Europe. It documents the main economic debates on cultural integration, and provides descriptions of the integration process in 7 main European countries.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Immigrants -- Cultural assimilation -- Europe; Europe -- Economic integration